2023
DOI: 10.30656/jak.v10i1.5439
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis Of ESG Disclosure On Green Finance Performance In Indonesia, Malaysia & Singapore Exchanges

Abstract: Green Finance in the banking sector is a new issue in the financial world because it is considered capable of increasing economic growth, by conserving natural resources so that economic development continues to be sustainable. This study aims to determine what factors affect financial performance in disclosing ESG items, so that company management can imply the results of this study which are expected to provide direct or indirect benefits for companies in the banking sector. The author collects independent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Additionally, the focus on traditional financial performance metrics may overshadow the importance of green finance in enhancing a bank's financial performance (Chowdhury, 2023). Furthermore, the complexity of integrating green finance practices into existing banking operations and products may deter researchers from exploring this area (Aulia et al, 2023). Overall, these factors contribute to the scarcity of research topics on green finance in banking.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the focus on traditional financial performance metrics may overshadow the importance of green finance in enhancing a bank's financial performance (Chowdhury, 2023). Furthermore, the complexity of integrating green finance practices into existing banking operations and products may deter researchers from exploring this area (Aulia et al, 2023). Overall, these factors contribute to the scarcity of research topics on green finance in banking.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ESG disclosure plays a crucial moderating role by mitigating the negative effect of business weaknesses and attenuating the positive effect of strengths (Fatemi et al, 2018). Along these lines, (Aulia et al, 2023) analyzed what factors affect FP in the disclosure of ESG elements in banks in three Asian countries. They found that the main challenge in implementing green investment was lack of incentives from the government and stakeholders.…”
Section: Introductionmentioning
confidence: 99%